Analysis of Changes in the Carrying Capacity of Food Agriculture in Kulon Progo Regency, Yogyakarta - Sukri, Irwansyah; Harini, Rika; Sudrajat, Sudrajat (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Abstract: The increase in the population impacts the increasing demand for food and non-food. Hence, to fulfill non-food needs, agricultural food land is converted into non-agricultural. It affected the carrying capacity of food agriculture. This paper aimed to analyze changes in the carrying capacity of food agriculture and the factors that influence the carrying capacity of food agriculture in the Kulon Progo Regency. This study used a descriptive-quantitative approach with spatial-temporal analysis techniques on secondary data, including population, rice field area, and rice field productivity for 2011, 2015, and 2019. The results showed that in 2011 Kulon Progo Regency could not be self-sufficient in food. However, in 2015, the research area had a great carrying capacity for food agriculture and continues to increase. This increase was influenced by the addition of rice fields and increased productivity. On the other hand, the reduction of rice fields decreased the productivity of rice fields, and the increase in the population led to a decrease in the carrying capacity of food agriculture in the Nanggulan, Kalibawang, and Samigaluh Districts. The rice field area and the productivity of rice fields affect food availability, while the population affects food needs. This paper showed that land-use changes in agri-food land (rice field area and productivity of rice fields) and the number of populations resulted in changes in the carrying capacity of food agriculture. Keywords: Carrying capacity, land use change, food self-sufficiency, rice field, population growth